Fluctuations of planted area in salt production in Bima Regency - Nur Ervina Meylani (PAKIS JOURNAL INSTITUTE, 2023)
This study aimed to analyze fluctuations in the planting area of salt production in the Bima district over six years. The data used were planting area data for the period 2016 – 2021. The results of this study showed that the highest planting area was in 2018, which was 1729.82 Ha and the lowest was in 2016, which was 435.78 Ha. The planting area is differentiated based on the type of production: non pugar, traditional Pugar, and geoisolator Pugar. The planting area for the highest non-Pugar production was in the Lambu sub-district, which was 20 ha and dominated by 63%. The planting area for the highest traditional Pugar production was found in the Woha sub-district, which was 653.02 Ha or 48% of the total planted area in Bima District. And for salt production in the geoisolator Pugar, the highest planting area is in Bolo District, which is 200.15 Ha and dominates as much as 48% of the total planted area as a whole for this type of production.